Does impaired O2 delivery during exercise accentuate central and peripheral fatigue in patients with coexistent COPD-CHF? - Oliveira, Mayron F.; Zelt, Joel T. J.; Jones, Joshua H.; Hirai, Daniel M.; O'Donnell, Denis E.; Verges, Samuel; Neder, J. Alberto (Frontiers in Physiology, 2015)
Impairment in oxygen (O2) delivery to the central nervous system (“brain”) and skeletal locomotor muscle during exercise has been associated with central and peripheral neuromuscular fatigue in healthy humans. From a clinical perspective, impaired tissue O2 transport is a key pathophysiological mechanism shared by cardiopulmonary diseases, such as chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF). In addition to arterial hypoxemic conditions in COPD, there is growing evidence that cerebral and muscle blood flow and oxygenation can be reduced during exercise in both isolated COPD and CHF. Compromised cardiac output due to impaired cardiopulmonary function/interactions and blood flow redistribution to the overloaded respiratory muscles (i.e., ↑work of breathing) may underpin these abnormalities. Unfortunately, COPD and CHF coexist in almost a third of elderly patients making these mechanisms potentially more relevant to exercise intolerance. In this context, it remains unknown whether decreased O2 delivery accentuates neuromuscular manifestations of central and peripheral fatigue in coexistent COPD-CHF. If this holds true, it is conceivable that delivering a low-density gas mixture (heliox) through non-invasive positive pressure ventilation could ameliorate cardiopulmonary function/interactions and reduce the work of breathing during exercise in these patients. The major consequence would be increased O2 delivery to the brain and active muscles with potential benefits to exercise capacity (i.e., ↓central and peripheral neuromuscular fatigue, respectively). We therefore hypothesize that patients with coexistent COPD-CHF stop exercising prematurely due to impaired central motor drive and muscle contractility as the cardiorespiratory system fails to deliver sufficient O2 to simultaneously attend the metabolic demands of the brain and the active limb muscles.